1988
DOI: 10.1021/ie00083a009
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous catalysis in the oxidation of p-chlorophenol in supercritical water

Abstract: The kinetics of the uncatalyzed and homogeneously catalyzed oxidation of p-chlorophenol in water near the critical point (374 °C, 218 atm) was investigated. Under the conditions of the experiments, the rate of disappearance of chlorophenol appears to be first order at low concentrations, second order at high concentrations, and independent of the concentration of oxygen. This was observed at both subcritical and supercritical conditions. Trace metals as a result of reactor corrosion were found in the reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(120 citation statements)
references
References 7 publications
3
117
0
Order By: Relevance
“…In a more recent study involving a model organic pollutant, Yang and Eckert (1988) oxidized p-chlorophenol in near-critical and supercritical water in a plug-flow reactor. They examined the dependence of the average reaction rate (average rate = A[p-chlorophenol]/.r) on the p-chlorophenol and oxygen concentrations, and reported that the reaction was first order in p-chlorophenol at low concentrations, second order at high concentrations, and always zero order in oxygen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a more recent study involving a model organic pollutant, Yang and Eckert (1988) oxidized p-chlorophenol in near-critical and supercritical water in a plug-flow reactor. They examined the dependence of the average reaction rate (average rate = A[p-chlorophenol]/.r) on the p-chlorophenol and oxygen concentrations, and reported that the reaction was first order in p-chlorophenol at low concentrations, second order at high concentrations, and always zero order in oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…did not report the conversions for each experiment, but she did report that the maximump-chlorophenol conversion was 95%. If the conversions from many of the experiments were frequently high, then the rate constants reported by and Yang and Eckert (1988) must be viewed as being only approximate.…”
Section: Introductionmentioning
confidence: 99%
“…The same was found for phenol (Thornton and Savage, 1990), acetamide, and acetic acid . In light of our results, it is interesting to note that Yang and Eckert (1988) found a reaction order for p-chlorophenol that increased from 1 to 2 as concentration was increased.…”
Section: 4mentioning
confidence: 50%
“…First-order dependence of the rate on the concentration of the organic component was reported in the literature for supercritical-water oxidation Tester, 1987, 1988;Yang and Eckert, 1988;Webley and Tester, 1989). Thus, we assume that the rate is given by r = k, exp( -E,,,/RT)C,, where A (the organic component) is the limiting reactant.…”
Section: Aiche Journalmentioning
confidence: 76%